Selective Production of Xylooligosaccharides by Xylan Hydrolysis Using a Novel Recyclable and Separable Furoic Acid - Zhao, Jianglin; Zhang, Xiaotong; Zhou, Xin; Xu, Yong (Frontiers in Bioengineering and Biotechnology, 2021)
Xylooligosaccharides, have gained considerable attention as prebiotics worldwide due to their immune strengthening activity and beneficial gut bacteria development and can be produced from xylan rich resources by acidic hydrolysis. The present study proved the organic acid hydrolysis to be beneficial for xylooligosaccharides yield. In this study, a recyclable and separable organic acid, i.e., furoic acid, was used for hydrolyzing xylan to produce xylooligosaccharides, and the response surface methodology design was applied to maximize the xylooligosaccharides yield, which resulted in a maximum yield was 49.2% with 1.2% furoic acid at 167 °C for 33 min. Meanwhile, the primary byproducts, including xylose and furfural, were concurrently bio-oxidized into xylonic acid and furoic acid by Gluconobacter oxydans and separated by electrodialysis. Subsequently, the furoic acid with low solubility (<3.7% 25 oC) was recovered by natural-crystallization. The above results indicate that the use of multi-steps contributes to sustainable XOS production by furoic acid.